Surface deformation and rebound for normal single-particle collisions in a surrounding fluid. (3rd June 2019) - Ruiz-Angulo, Angel; Roshankhah, Shahrzad; Hunt, Melany L.
Abstract : This article presents experimental measurements involving immersed collisions between a rigid impactor and a deformable target for a wide range of Reynolds and Stokes numbers. Three aluminium alloys are used as solid targets submerged in seven different fluids covering a wide range of viscosity and density. The collision and rebound velocities as well as the depth and diameter of the crater produced by the collisions are measured with high resolution. Most of the experiments in this study occur at velocities for which the deformation is within the elastic–plastic regime. Results of the experiments in air are analysed by elastic, plastic and elastic–plastic theories, and demonstrate the complexities of modelling elastic–plastic collisions. For collisions in a liquid, the measurements show that the size of the crater is independent of the fluid characteristics if the Stokes number is beyond a critical value. The normal coefficient of restitution can be estimated by including both viscous losses and plasticity effects and assuming that the collision time scale is significantly shorter than the hydrodynamic time scale. The results of the crater dimensions are also used to develop an analytical expression for the volume of deformation of the material as a function of material properties and the impact and critical Stokes numbers.